THE EXERCISE FOR DIABETES MELLITUS TYPE 2 - Awan Dramawan; Cembun Cembun; Akhmad Fathoni (Jurnal Kesehatan Prima, 2016)
Abstract : Diabetes mellitus type 2 is caused by insulin resistance, thus it produces hyperglicemia (blood glucose > 126 mg/dl) and usually occurs in weight more than normal (Soeparman, 1991; Christine, 2002). The exercise is an activity which is useful for diabetic as it can reduce blood glucose. When exercising, the body needs energy which is mostly obtained from glucose in body. While exercising, there is enhancement of power needs. Therefore, the glucose level in body will reduce because of that activity. The exercise is useful to the body is not just any sport activities, it can be said useful if there is achievement of target pulse, it does not seen from fatigue which is felt or amount of sweat that is produced. When the pulse to be achieved can stimulate organ function, the body will always respond each burden and accustomed with FITT (frequency, intensity, time and type), in terms of frequency 3 times a week, aerobic intensity 60-70% DNM, time 20-30 minutes, and type; jogging, run and other types of exercises (Wiarto, 2013). The advantage of exercise is to control blood-glucose, enhance high-quality cholesterol level (HDL), lose weight, improve musculoskeletal symptoms, improve quality of life, and prevent the occurence of diabetes mellitus. If the exercise is concucted appropriately, thus the indicator of its success is fasting blood glucose 80 to < 100 mg/dL, blood glucose after meal 80 to <145 mg/dL, HbAlc < 7%, LDL < 100 mg/dL, HDL for men ≥ 40 mg/dL, for women ≥ 50 mg/dL, trigliserida < 150 mg/dL, total cholesterol < 200 mg/dL, and blood pressure is 120/80 mmHG (Suryono E, 2013)).